Suomalaisten etunimet - Kiviniemi, Eero (Suomalaisen Kirjallisuuden Seuran toimituksia, 2006)
Summary.
Keywords: 1800-luku; etunimet; etymologia; henkilönnimet; historia; nimet; nimistöntutkimus; suomen kieli; suosio; valinta; Suomi; nimenvalinta